Adherence to the RSA and CT-RSA guideline items in clinical prosthesis migration studies: a systematic review - Thies J N van der Lelij; Lennard A Koster; Bart L Kaptein; Rob G H H Nelissen; Perla J Marang-van de Mheen (Acta Orthopaedica)
Background and purpose: Standardized reporting on methodology and results in clinical RSA research papers facilitates evaluation of quality and interpretation of results. We aimed to assess the extent to which radiostereometric analysis (RSA) and computed tomography-based RSA (CT-RSA) studies adhered to the items of the new RSA reporting guideline from 2024. Methods: A systematic literature search was performed to identify all clinical RSA studies published between January 2012 and February 2024. Studies were eligible for inclusion if prosthesis migration over time was assessed. The adherence of studies to each applicable guideline item (full, partial, or no) was assessed. Results: 285 studies were included, most of which assessed prosthesis migration in the hip (n = 161) or knee (n = 99). No study reported on all guideline items. The mean (full or partial) adherence of studies to all (applicable) items was 61% (standard deviation [SD] 11). Large variation between the reporting of items was found, ranging from being reported in 1% of the studies to 100%. The least reported items in studies were the mean number and SD of days between surgery and baseline RSA examination (8% of studies), mean number and SD of days between surgery and primary endpoint RSA examination (1%), and consistent- or all-marker method for RSA analysis (3%). Conclusion: Current studies on average reported only 61% of the items from the updated RSA guidelines. Adherence to the guidelines in clinical RSA studies on prosthesis migration should be improved, in order to improve the quality of studies and the interpretation of outcomes on implant migration.